The party and the people : Chinese politics in the 21st century - Dickson, Bruce J. (Princeton University Press, 2021)
"Since 1949, the Chinese Communist Party (CCP) has maintained an unrivaled grip over the country. Despite economic calamity, widespread social upheaval, and even violence against its own people, the party has overseen the fastest economic growth in history and only strengthened its hold on power. How has it achieved this, and how exactly does the party and the government function? What is political life like for the people of China, and how has this changed over the decades of the party's rule? Is democracy on the horizon? These are some of the questions that animate Bruce Dickson's exploration of Chinese politics today. At the core of the party's practices is a dual approach--repression when faced with existential, political threats, and responsiveness when faced with more localized economic or social unrest. Yet while the regime is responsive to a degree often unacknowledged by international observers, ultimately it is not accountable to the public. The opportunity for the public to chose leaders is limited to very local levels, and it is the party itself that chooses when to compromise and when to repress. Dickson uses this lens to illuminate a number of key questions: How are leaders chosen and how are policies made? When is protest and civic engagement allowed, and when is it suppressed? Acknowledging that the inner workings of the party remain shrouded in secrecy, Dickson draws from the full landscape of sources available to lay out what we know and what the future may hold as Xi's rule extends and takes an increasingly repressive approach to governing"--